Perlindungan Hukum Bagi Member SJ Travel Pass Terhadap Perjanjian Baku Dalam Program Keanggotaan Khusus Jasa Angkutan Penerbangan (Studi Kasus SJ Travel Pass) - Fathurian Ramadhan; Mustolih Siradj; Maman Rahman Hakim (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study examines the validity and legality of the standard agreement in the SJ Travel Pass special membership program on flight transportation services, as well as the legal protection for disadvantaged members. This study uses normative legal research on statutory standards. Using library research, the adopted strategy is both statutory and case-based. Reading, evaluating, characterizing, and analyzing library resources was done to generate relevant papers. This study concludes that the SJ Travel Pass standard agreement will be electronic. The contract is void under Article 1320 of the Civil Code and Law 19 of 2016 amending Law 11 of 2008 on Information and Electronic Transactions because it does not meet the objective requirements of Law 8 of 1999 on Consumer Protection, namely the inclusion of standard clauses prohibited under Article 18 section (1) letters g and f. The contract is void. Consumer protection compels Sriwijaya to compensate customers without criminal culpability or fines. The Indonesian Consumers Foundation has mediated (non-litigious) disputes. Consumers can fight for their rights by applying to the Consumer Dispute Settlement Agency or Arbitration Institution, filing a legal case with the District Court, and/or reporting fraud and embezzlement.